‘A MALAY KNIGHT SPEAKS THE WHITE MAN’S TONGUE’ - AN ANALYSIS OF MUHAMMAD HA JI SALLEH AS A TRANSLATOR - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 28 November 2016 – Having served at USM from 19721974, Harry Aveling makes it a point to take time out of his busy schedule to come to Universiti Sains Malaysia (USM) whenever he is in the country.